Exoplanetary Monte Carlo radiative transfer with correlated-k – I. Benchmarking transit and emission observables. Issue 2 (23rd May 2019) - Lee, Graham K H; Taylor, Jake; Grimm, Simon L; Baudino, Jean-Loup; Garland, Ryan; Irwin, Patrick G J; Wood, Kenneth
Abstract: Current observational data of exoplanets are providing increasing detail of their 3D atmospheric structures. As characterization efforts expand in scope, the need to develop consistent 3D radiative-transfer methods becomes more pertinent as the complex atmospheric properties of exoplanets are required to be modelled together consistently. We aim to compare the transmission and emission spectra results of a 3D Monte Carlo radiative transfer (MCRT) model to contemporary radiative-transfer suites. We perform several benchmarking tests of an MCRT code, Cloudy Monte Carlo Radiative Transfer (cmcrt ), to transmission and emission spectra model output. We add flexibility to the model through the use of k -distribution tables as input opacities. We present a hybrid MCRT and ray tracing methodology for the calculation of transmission spectra with a multiple scattering component.cmcrt compares well to the transmission spectra benchmarks at the 10s of ppm level. Emission spectra benchmarks are consistent to within 10 per cent of the 1D models. We suggest that differences in the benchmark results are likely caused by geometric effects between plane-parallel and spherical models. In a practical application, we post-process a cloudy 3D HD 189733b GCM model and compare to available observational data. Our results suggest the core methodology and algorithms ofcmcrt produce consistent results to contemporary radiative transfer suites. 3D MCRT methods are highly suitable for detailed post-processing of cloudy and non-cloudy 1D and 3D exoplanet atmosphere simulations in instances where atmospheric inhomogeneities, significant limb effects/geometry or multiple scattering components are important considerations.